DINAMIKA SISTEM KEBIJAKAN PENDIDIKAN BAHASA INDONESIA DAN IMPLEMENTASINYA DALAM PEMBELAJARAN DI KELAS - Cecep Wahyu Hoerudin (GoAcademica Research dan Publishing, 2021)
To be able to develop their potential, humans need education through the learning process. Language is a very important part of education, because of its function as a means of communication and introduction in the world of education. Therefore, policies in language education must be formulated in a comprehensive and visionary manner so that their implementation can be optimized and contribute to realizing the goals of national education. On the other hand, education policies must also accommodate the proportional use of the Indonesian language. This research will be carried out using a qualitative approach and data sourced from various previous studies and studies. The results of this study found that language design as an effort to develop language in a more advanced direction includes three processes, namely design, implementation and evaluation. Indonesian has a position as the National Language and as the State Language.